Development of local wisdom-based flipbook to strengthen tolerance in elementary school - Juliana Dwi Arifin Lubis; Surya Dharma; Anita Yus (Himpunan Pengembang Kurikulum Indonesia, 2025)
Flipbook in elementary schools serves as an interactive medium that helps present learning materials attractively and strengthens students’ understanding. This study aims to examine the results of developing a Flipbook pocketbook based on North Sumatran local wisdom, which is feasible, practical, and effective in fostering tolerant attitudes among students at SDN 101802 Namorambe. The research employed a Research and Development approach using the Borg and Gall model, which includes the stages of identifying problems, designing and developing products, and testing products. The feasibility of the media was assessed by experts in content, design, and language, all of whom provided evaluations that placed the product in the highly feasible category. The practicality of the Flipbook pocketbook was tested through trials involving students of different levels, and the results showed that the product met the criteria of practicality in both individual and small group settings. The effectiveness of the Flipbook was evaluated through pre-test and post-test activities conducted in two elementary schools, which demonstrated a clear improvement in students’ tolerance attitudes. Based on these findings, it can be concluded that the developed Flipbook pocketbook, grounded in North Sumatran local wisdom, is feasible, practical, and effective in fostering tolerance among elementary school students. Abstrak Flipbook di sekolah dasar berfungsi sebagai media interaktif yang membantu menyajikan materi pembelajaran secara menarik dan memperkuat pemahaman siswa. Penelitian ini bertujuan untuk mengkaji hasil pengembangan buku saku Flipbook berbasis kearifan lokal Sumatera Utara yang layak, praktis, dan efektif dalam menumbuhkan sikap toleransi pada siswa di SDN 101802 Namorambe. Penelitian ini menggunakan pendekatan Penelitian dan Pengembangan dengan model Borg dan Gall, yang meliputi tahapan identifikasi masalah, perancangan dan pengembangan produk, dan uji coba produk. Kelayakan media dinilai oleh para ahli dalam konten, desain, dan bahasa, yang semuanya memberikan evaluasi yang menempatkan produk dalam kategori sangat layak. Kepraktisan buku saku Flipbook diuji melalui uji coba yang melibatkan siswa dari berbagai tingkat, dan hasilnya menunjukkan bahwa produk tersebut memenuhi kriteria kepraktisan baik dalam pengaturan individu maupun kelompok kecil. Efektivitas Flipbook dievaluasi melalui kegiatan pra-tes dan pasca-tes yang dilakukan di dua sekolah dasar, yang menunjukkan peningkatan yang jelas dalam sikap toleransi siswa. Berdasarkan hasil temuan tersebut dapat disimpulkan bahwa buku saku Flipbook berbasis kearifan lokal Sumatera Utara yang dikembangkan layak, praktis, dan efektif untuk memperkuat toleransi siswa Sekolah Dasar. Kata Kunci: buku saku; flipbook; kearifan lokal; sikap toleransi